Analyzing Migration Across Literature: Russian Émigré Literature in the Texts of A. Averchenko and Z. Shakhovskaya - Erinç, Erdem (Border Crossing, 2017)
This paper uses historical resources, extensively, from the texts of Russian émigré authors A. Averchenko and Z. Shakhovskaya who both wrote on two of the main refugee migrant evacuations out of Russia to Istanbul. The aim was to reveal the role of literary texts in forming a better understanding of the dynamics of such evacuations. The main reason for choosing the above authors’ texts (Notes of a Fool by A. Averchenko and Life Style from the book “Takov moi vek” by Z. Shakhovskaya) was that they were written about two very different evacuations, although both took place during the same first wave of Russian migration. The first is known as General Denikin’s and the second as General Wrangel’s evacuation. The authors were also chosen because of their different age and gender. Analyzing author’s literary texts about differing types, refugee migrant evacuations provides an opportunity to evaluate the dynamics of such evacuations, as well providing an opportunity to read history from another perspective, utilizing various factors and variables such as time, generation and gender.